The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3389/fchem.2020.00548
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Bifidobacterium bifidum in Feces Sample by Highly Sensitive Quartz Crystal Microbalance Immunosensor

Abstract: In this work, a quartz crystal microbalance (QCM) sensor has been fabricated using immunoassay for sensitive determination of Bifidobacterium bifidum. Au nanoparticle has been used for amplifying sandwich assays. The proposed immunosensor exhibited a linear detection range between 10 3 and 10 5 CFU/mL with a limit of detection of 2.1 × 10 2 CFU/mL. The proposed immunosensor exhibited good selectivity for B. bifidum sensing with low cross reactivity for other foodborne pathogens such as Lactobacillus acidophilu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…The highest detectable cell concentration was 5 × 10 5 CFU/mL [ 106 ]. A concentration within this measuring range, namely, 10 4 CFU/mL B. bifidum in about 50× diluted milk, was tested using a sandwich assay with gold-labeled antibodies [ 114 ]. The dilution successfully reduced interferences from the milk proteins, but the LOD in undiluted milk was correspondingly higher.…”
Section: Application Of Baw and Saw Sensors And Biosensors In Milk Me...mentioning
confidence: 99%
See 1 more Smart Citation
“…The highest detectable cell concentration was 5 × 10 5 CFU/mL [ 106 ]. A concentration within this measuring range, namely, 10 4 CFU/mL B. bifidum in about 50× diluted milk, was tested using a sandwich assay with gold-labeled antibodies [ 114 ]. The dilution successfully reduced interferences from the milk proteins, but the LOD in undiluted milk was correspondingly higher.…”
Section: Application Of Baw and Saw Sensors And Biosensors In Milk Me...mentioning
confidence: 99%
“…The target oligonucleotides obtained via PCR were detected using a QCM sensor coated with the corresponding oligonucleotides. This was followed by sandwich hybridization with gold-labeled oligonucleotides to enhance the mass load [ 120 ], similar to the sandwich assay described before ( Table 4 ) for the detection of B. bifidum [ 114 ]. Measurements in buffer showed that the sandwich hybridization with gold labels allowed the reduction of the LOD for E. coli to 1.2 × 10 2 CFU/mL, which is two orders of magnitude lower than that obtained using direct detection of the oligonucleotides.…”
Section: Application Of Baw and Saw Sensors And Biosensors In Milk Me...mentioning
confidence: 99%
“…In recent years, food poisoning caused by foodborne pathogens has frequently occurred worldwide, which is the most prominent public health problem in the world (Hou et al, 2020;Duan et al, 2021). As one of the most hazardous foodborne pathogens, Escherichia coli (E. coli) O157:H7 can cause some diseases such as hemorrhagic colitis and hemolytic uremic syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…At present, phosphotungstic acid reduction (PAR) method, HPLC, enzyme method, and electrochemical sensor have been established in clinical setting to detect UA. The principle of determination of UA by PAR is that under alkaline conditions, phosphotungstic acid reacts with UA to produce tungsten blue and allantoin (Feng et al, 2020 ; Hou et al, 2020 ; Karimi-Maleh et al, 2020a ). The concentration of UA is indirectly obtained by colorimetry.…”
Section: Introductionmentioning
confidence: 99%